(untitled) (Periphērica: Revista de Historia Social, Cultural, y Literaria, 2024)
This article argues that recent poetry collections by two poets from the Mexican state of Guerrero, the Mè’phàà poet Hubert Matiúwàa’s (1986) and the Nahua poet Martín Tonalmeyotl (1983) respond to the violence of the ongoing drug war in México by mobilizing Indigenous ritual textualities. In doing so, both Matiúwàa’s Xtámbaa/Piel de Tierra (2016), literally “earthen skin,” and Tonalmeyotl’s Tlalkatsajtsilistle/ Ritual de los olvidados (2016) leverage Indigenous epistemological practices as a way to alter reality. This analysis not only aligns their respective projects with longstanding Indigenous language practices in Mesoamerica and elsewhere, but also situates them within broader contemporary Indigenous movements, in which Indigenous authors use their ostensibly literary texts to intervene directly in the world of the reader.